Rev. Proc. 2020-29 (United States. Internal Revenue Bulletin, 2020)
PURPOSE This revenue procedure modifies the procedures in Rev. Proc. 2020-1, 2020-1 I.R.B. 1 (Jan. 2, 2020), temporarily to allow for the electronic submission of requests for letter rulings, closing agreements, determination letters, and information letters under the jurisdiction of the Internal Revenue Service (IRS) Office of Chief Counsel, and for determination letters issued by the IRS Large Business and International Division (LB&I). [...]this revenue procedure is modified or superseded, both paper and electronic requests for advice described in section 2.01 of this revenue procedure provided by Associate Chief Counsel Offices and LB&I, as defined in section 2.02 of this revenue procedure, will be accepted. Rev. Proc. 2020-1 generally requires taxpayers to submit paper copies of written materials with wet signatures. .02 For purposes of this revenue procedure, the term Associate Chief Counsel Offices and LB&I collectively refers to the following Associate Chief Counsel offices and LB&I: the Associate Chief Counsel (Corporate), the Associate Chief Counsel (Financial Institutions and Products), the Associate Chief Counsel (Income Tax and Accounting), the Associate Chief Counsel (International), the Associate Chief Counsel (Passthroughs and Special Industries), the Associate Chief Counsel (Procedure and Administration), and the Associate Chief Counsel (Employee Benefits, Exempt Organizations, and Employment Taxes). [...]the IRS encourages taxpayers and their representatives to use a secure electronic facsimile service for transmitting requests for advice. To compress and encrypt email attachments, follow the directions provided by the program. Because these programs do not encrypt the subject line, the body of the email, or the file name of the attachment, all taxpayer information, including the name of the taxpayer, and return information should be included only in the encrypted attachment.